Literary critical-speeches in Chile: Lastarria and Bello “As critical developed” - Doll Castillo, Darcie (ALPHA. Revista de Artes, Letras y Filosofía, 2019)
This article examines the argument that locates the beginning of critical and literary discoursiveness in Chile in the consolidation of Latin American independence processes in the first half of the 19th century in the writings of Andrés Bello and José Victorino Lastarria. The study proposes that Bello’s criticism, as regards the relationship between the attachment to rhetoricity and his notion of historical knowledge, provides criticism with a project related to its emancipatory tenets as shown in the postulatory function of Bello’s criticism. On the other hand, considering his foundational zeal and his interpretative conception of history, Lastarria contributes to an emphatic and stable inscription of the interpretative function for the configuration of future critical and literary discourses.